Entre descanso e sociabilidades: uma etnografia sobre o lazer no cotidiano de mulheres em situação de rua em Belo Horizonte - MG - Jordania de Oliveira Eugenio (2023)
Based on the conception that leisure, inseparable from the time-space in which it manifests itself, is inherent to the life of any person, the objective of this thesis is to identify and describe how leisure is present in the daily lives of homeless women who attend the Integrated Women's Service Center (CIAM) in Belo Horizonte – MG. Based on an ethnographic study carried out with homeless women, users of a multisectoral public facility linked to Belo Horizonte City Hall, I show which leisure practices are present in these women's daily lives, as well as what understandings they have about the phenomenon. Leisure in their daily lives is expressed, within CIAM, through the rest of their bodies and minds, as well as in the sociability that takes place in the context of the Center; on the streets, leisure is present by means of different activities that emerge among these women, amusing them and relieving – even if momentarily – the tensions caused by living on the streets. In line with what the data collected – through the practice of participant observation as well as the exercise of describing what was often left unsaid – this research defends the idea that the leisure practices of homeless women, interlocutors of this research, by enabling the enjoyment of their lives, bring them closer to moments of dignity, which is essential for the experience and survival of this social group.